2023
DOI: 10.1037/adb0000921
|View full text |Cite
|
Sign up to set email alerts
|

Examining indirect effects of advertising exposure on young adults’ cannabis and nicotine vaping.

Abstract: Objective: To examine longitudinal associations between exposure to two types of advertisements (medical/recreational cannabis and e-cigarette retailers [vape shops]) and young adults’ cannabis and nicotine vaping behavior. Positive and negative expectancies for cannabis and vaping nicotine were examined as mediators of these associations. Method: Secondary analysis of observational data from a longitudinal cohort of young adults recruited from Southern California (Wave 13: N = 2,411, 56% female, Mage = 23.6).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Therefore, educational campaigns to raise youth awareness of e-cigarette harms and strict regulations of advertising campaigns should be encouraged to reduce the ability of the campaigns to solicit curiosity as a marketing strategy. Previous studies did not reach consistency on whether harm perception mediates the relationship between advertising exposure and e-cigarette use 8,[11][12][13] . The current study provides no evidence to support the mediating role of harm perception in the Chinese young adult never smoker population, consistent with two longitudinal studies that did not support those beliefs about health outcomes of vaping significantly mediating the relationship between advertising exposure and young adult use 12,13 .…”
Section: Curiosity Mediates Advertising Exposure and E-cigarette Usementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, educational campaigns to raise youth awareness of e-cigarette harms and strict regulations of advertising campaigns should be encouraged to reduce the ability of the campaigns to solicit curiosity as a marketing strategy. Previous studies did not reach consistency on whether harm perception mediates the relationship between advertising exposure and e-cigarette use 8,[11][12][13] . The current study provides no evidence to support the mediating role of harm perception in the Chinese young adult never smoker population, consistent with two longitudinal studies that did not support those beliefs about health outcomes of vaping significantly mediating the relationship between advertising exposure and young adult use 12,13 .…”
Section: Curiosity Mediates Advertising Exposure and E-cigarette Usementioning
confidence: 99%
“…Previous studies did not reach consistency on whether harm perception mediates the relationship between advertising exposure and e-cigarette use 8,[11][12][13] . The current study provides no evidence to support the mediating role of harm perception in the Chinese young adult never smoker population, consistent with two longitudinal studies that did not support those beliefs about health outcomes of vaping significantly mediating the relationship between advertising exposure and young adult use 12,13 . In contrast, some research found that higher exposure to e-cigarette advertisements led to lower harm perception of e-cigarettes among youth, which further increased their probability of future use 8,11 .…”
Section: Curiosity Mediates Advertising Exposure and E-cigarette Usementioning
confidence: 99%
See 1 more Smart Citation